Evaluation of Interleukin-10 Levels in Patients Diagnosed with Chronic Hepatitis - Ozguler, M.; Akbulut, H. H.; Akbulut, A. (Univ West Indies Faculty Medical Sciences, 2015)
Objective: One of the most important factors playing a role in chronic hepatitis B pathogenesis is cytokine release and one of the cytokines with anti-inflammatory characteristic is interleukin-10 (IL-10). The aim of the present study is to examine IL-10 levels in patients with chronic hepatitis B. Subjects and Methods: Sixty-three patients with chronic hepatitis B disease who had not received any antiviral treatment were included in the study. Serum IL-10 level was investigated by enzyme-linked immunosorbent assay (ELISA) method. In the control group, 25 healthy individuals with mean age similar to the patient population were included. Control and patient groups were compared and data were statistically analysed. Results: Interleukin-10 levels of 25 patients with hepatitis B virus (HBV) DNA levels between 2000 and 20 000 IU/mL were compared with those of 25 subjects in the control group, and the level in the chronic hepatitis B group was statistically significantly higher (p < 0.05). Interleukin-10 levels of 38 patients with HBV DNA > 20 000 IU/mL were statistically significantly higher than those in the control group. When chronic hepatitis B patients were compared among themselves, IL-10 levels increased as HBV DNA levels increased. Also, when IL-10 levels of hepatitis B 'e' antigen (HBeAg) positive patients were compared with those of HBeAg negative patients, the difference was not statistically significant. Conclusion: It is believed that decreasing IL-10 levels by various methods would have significant contributions in disease progression and treatment. Moreover, IL-10 level may be an important marker in HBeAg seroconversion and evaluation of treatment response.
Keywords: Chronic hepatitis B; cytokine; interleukin-10